Epigenetic silencing status of p16INK4a and MGMT promoter regions identified qualitatively in diffuse large B cell lymphoma - Mohd Ridah, L Jalilah; A.Talib, Norlelawati; Hussain, Faezahtul Arbaiyah; Zainuddin, Norafiza (Karger, 2015)
Apart from genetic mutation, DNA methylation, an epigenetic event, has emerged as an important genomic disorder which silences the gene through addition of methyl group to the cytosines especially in CpG islands located in promoter region. p16, a tumor suppressor gene that inhibits cyclin-dependent kinase, inactivates the Rb protein and blocks G1 phase in a normal cell cycle. A DNA repair gene, MGMT removes alkyl adduct to a cysteine residue within the protein, thus preventing mutagenic effects and lethal crosslinks. Methylation silencing of p16 and MGMT has been reported to associate with pathogenesis of DLBCL significantly. We aimed to screen for p16 and MGMT methylation status in DLBCL cases. Methylation status in DLBCL cases were screened using methylation specific PCR (MSP). p16 methylation was identified in 64 (73%) of 88 samples. Interestingly, MGMT methylation was detected in all cases. We found an association between p16 methylation status with patients aged >50 years old (p = 0.023). This finding is parallel with an animal study demonstrating that aging increases p16 methylation, however disconcordant to the fact, which has been revealed decades ago, thatp16 expression increases with aging. Yet to be noted, p16 methylation is not the sole determinant of p16 expression. MGMT methylation was reported to be strongly related with cancer patients who smoke, drink and are non-vegetarian. Thus, it is hypothesized that lifestyle might also trigger MGMT methylation in this study population. Conclusion: Our findings indicate that p16 and MGMT methylation were associated with DLBCL.